Characterization and modeling of atomic layer deposited high-density trench capacitors in silicon - Matters-Kammerer, Marion K. (2013)
A detailed electrical analysis of multiple layer trench capacitors fabricated in silicon with atomic-layer-deposited Al2O3 and TiN is presented. It is shown that in situ ozone annealing of the Al2O3 layers prior to the TiN electrode deposition significantly improves the electric properties of the devices such as the dielectric constant, leakage current, and the breakdown voltage of the devices. The self-inductance and self-resistance of the capacitors as derived from S-parameter measurements up to 10 GHz are very small, as low as 4 pH and 6 mΩ for 19.1 mm2 electrode surface. These data are shown to be consistent with a theoretical model.